2004
DOI: 10.1897/02-644
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury production in high arctic wetlands

Abstract: Mercury is present at elevated levels in the top predators living in High Arctic ecosystems. Because only methylmercury (MeHg) bioaccumulates in food chains, the sources need to be identified. In temperate environments, wetlands are considered to be the principal sources of MeHg, with sulfate-reducing bacteria (SRB) thought to be responsible. The present study investigated whether High Arctic wetlands produced MeHg and whether SRB were involved in MeHg formation. Frozen soil was collected from 18 High Arctic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 37 publications
8
44
0
1
Order By: Relevance
“…A study of Arctic wetland soils showed that MeHg concentrations increased 100-fold after thawing and incubating at typical Arctic summer temperatures (4 to 8 8C). [91] Although sulfatereducing bacteria are thought to be the predominant MeHg producers in temperate anoxic environments, the genes responsible for dissimilatory sulfate-reduction could not be detected from all the wetland sites studied. [91] This suggested either a methodological issue or that sulfate-reducers are in fact not the dominant microbial methylators in Arctic wetlands.…”
Section: Controls On Arctic Food Chain Mercury Accumulation By Methylmentioning
confidence: 83%
See 3 more Smart Citations
“…A study of Arctic wetland soils showed that MeHg concentrations increased 100-fold after thawing and incubating at typical Arctic summer temperatures (4 to 8 8C). [91] Although sulfatereducing bacteria are thought to be the predominant MeHg producers in temperate anoxic environments, the genes responsible for dissimilatory sulfate-reduction could not be detected from all the wetland sites studied. [91] This suggested either a methodological issue or that sulfate-reducers are in fact not the dominant microbial methylators in Arctic wetlands.…”
Section: Controls On Arctic Food Chain Mercury Accumulation By Methylmentioning
confidence: 83%
“…[91] Although sulfatereducing bacteria are thought to be the predominant MeHg producers in temperate anoxic environments, the genes responsible for dissimilatory sulfate-reduction could not be detected from all the wetland sites studied. [91] This suggested either a methodological issue or that sulfate-reducers are in fact not the dominant microbial methylators in Arctic wetlands. Results from a study of the biogeochemical cycling of MeHg in lakes and tundra watersheds of Alaska (688N) showed that the principal source of MeHg was in situ benthic production (80 to 91 % of total inputs), and that contributions from the tundra watershed snowpack and soils were modest.…”
Section: Controls On Arctic Food Chain Mercury Accumulation By Methylmentioning
confidence: 83%
See 2 more Smart Citations
“…Sulfate reducing bacteria (SRB) are considered to be the main Hg methylators in aquatic temperate ecosystems and may play a role in the Arctic soils, streams and lakes; however this assumption requires further testing. Loseto et al (2004b) collected sediments in Arctic wetlands prior to spring thaw. The MeHg concentration in the frozen sediments was low when they were transported to the laboratory (average 0.065 ng/g) but after incubation at 6 and 8 • C for 30 and 60 days, values increased up to 100 fold in some samples.…”
Section: Methylation Of Hg In Polar Regionsmentioning
confidence: 99%